Letter from Samuel W. Levis to James Curtis Booth, May 4, 1883 - Levis, Samuel W. (1883)
Samuel W. Levis writes to James Curtis Booth (1810-1888) following his letters of April to enquire after land for sale.
Keywords: Booth, James Curtis, 1810-1888; Real property; Levis, Samuel W.